2017
DOI: 10.1371/journal.pone.0170240
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Dysregulation in Hepacivirus Infection of Common Marmosets (Callithrix jacchus)

Abstract: Chronic hepatitis C has been associated with metabolic syndrome that includes insulin resistance, hepatic steatosis and obesity. These metabolic aberrations are risk factors for disease severity and treatment outcome in infected patients. Experimental infection of marmosets with GBV-B serves as a tangible, small animal model for human HCV infection, and while virology and pathology are well described, a full investigation of clinical disease and the metabolic milieu is lacking. In this study six marmosets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…In addition, the liver of all 4 animals exhibited virus-induced hepatitis. Our previous reports showed primary GBV-B infection could also induce lymphocytic infiltration along with fibrotic and steatotic changes even after clearance of viremia (Manickam et al, 2016; Manickam et al, 2017). In this study we observed mild (in 02–10) to severe (01–10) microscopic hepatitis and fibrotic lesions in all four re-infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the liver of all 4 animals exhibited virus-induced hepatitis. Our previous reports showed primary GBV-B infection could also induce lymphocytic infiltration along with fibrotic and steatotic changes even after clearance of viremia (Manickam et al, 2016; Manickam et al, 2017). In this study we observed mild (in 02–10) to severe (01–10) microscopic hepatitis and fibrotic lesions in all four re-infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…Progression occurs despite clearance of the virus from plasma [124,125]. These changes are associated with concomitant changes in plasma insulin and glucagon levels consistent with metabolic dysregulation [126]. While acute experimental infection is not associated with notable clinical signs, one may see an elevation in serum ALT, ALP, and/or LDH clinically.…”
Section: Gb Virusmentioning
confidence: 99%
“…Several C. jacchus models have been described for both spontaneous and experimentally induced obesity with hyperglycemia and hypertriglyceridemia. These marmoset models were generated with diverse agents, such as human adenovirus-36 (Ad-36) [ 100 ], GBV-B [ 101 ], adult high calorie diet [ 102 ], and exposure to glucocorticoids [ 103 ].…”
Section: Callithrix Jacchus Models Of Human LIVmentioning
confidence: 99%
“…They gained substantial weight in the 28-week period of the study, and blood samples revealed Ad-36 antibodies in the liver, and elevated serum levels of cholesterol and triglycerides [ 100 ]. In another investigation, marmosets that were infected intravenously with GBV-B, had a significant increase in their insulin, glucagon and glucagon-like peptide 1 in the plasma, became hypertriglyceridemic and had up to a 10-fold increase in adipocytokines [ 101 ]. In the liver, cytoplasmic changes associated with steatosis were observed at 168 days post-infection in all infected animals ranging from mild to severe steatosis.…”
Section: Callithrix Jacchus Models Of Human LIVmentioning
confidence: 99%
See 1 more Smart Citation